O Despertar Do Lótus - Terceira Coisa E Vivência De Si Em Ibn `Arabí - Johnson, Sandra Regina Benato [UNIFESP] (2017)
This work develops the concept of third thing in Ibn ‘Arabī as the sense of Identity anchored in the experience of self and daily living. Considering the simultaneous affirmation of every correlate pair, we treat the personal pronominal relations from the point of view of notions such as receptivity, transitivity, and analogy which the Sheikh establishes between the Necessary Being and the Perfect Human Being. This allows us to search for the fundamental philosophical principles of the Science of Barāzikh, here named Psicosofia, and how to actualize it as a kind of individuation’s hermeneutics and dynamics of interaction in the process of Reality.